2019
DOI: 10.1007/s42832-019-0008-8
|View full text |Cite
|
Sign up to set email alerts
|

Straw biochar strengthens the life strategies and network of rhizosphere fungi in manure fertilized soils

Abstract: Soil fungi have many important ecological functions, however, their life strategies and interactions in manure fertilized soils are not well understood. The aim of this study was to investigate the effects of biochar amendment on the fungal life strategies and species interactions in ryegrass (Lolium perenne L.) rhizosphere soil by high-throughput sequencing. Three soil treatments were evaluated: soil and pig manure mixture without planting ryegrass and biochar application (bulk soil), mixture with ryegrass pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…S7 ), most of the soil chemical variables were significantly and positively correlated with fungal community parameters but slightly and negatively correlated with bacterial community parameters. Generally, a more complex co-occurrence network could be developed following biochar addition to soil [ 74 ]. Similarly, in the present study, the nodes, edges, average path length and fungal network modularity all increased with biochar addition compared with MC ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S7 ), most of the soil chemical variables were significantly and positively correlated with fungal community parameters but slightly and negatively correlated with bacterial community parameters. Generally, a more complex co-occurrence network could be developed following biochar addition to soil [ 74 ]. Similarly, in the present study, the nodes, edges, average path length and fungal network modularity all increased with biochar addition compared with MC ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Soil microorganisms in biochar-amended soil could adapt to a wide range of micro-niches. In a work on straw biochar’s effect on the network of rhizosphere fungi by Wang et al (2019) , the nodes, edges, average path length, and fungal network modularity increased following biochar in addition to ryegrass soil. High-complexity networks normally tended better stability against environmental stresses with buffering through networking ( Landi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diverse and specific physiochemical characteristics of BC that influence soil microbial composition are increased labile carbon, pH, surface area for colonization, and water content in amended soils. BC addition induces remodeling of the microbial diversity and community structure of the soil; however, the changes are highly variable and dependent on the individual soil properties [146,147]. It was reported that low pyrolysis temperature BCs (>350 • C) harbor a greater number of organic residues and are commonly characterized by lower pH.…”
Section: Microbial Activitymentioning
confidence: 99%